2010
DOI: 10.1021/jf101415v
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in High-Fat Diet-Induced Obesity and Body Fat Accumulation by a Nelumbo nucifera Leaf Flavonoid-Rich Extract in Mice

Abstract: Diets high in fat lead to excessive lipid accumulation in adipose tissue, which is a crucial factor in the development of obesity, hepatitis, and hyperlipidemia. In this study, we investigated the antiobesity effect of a flavonoid-enriched extract from Nelumbo nucifera leaf (NLFE) in vivo. C57BL/6 mice were fed with a high-fat diet (HFD) to induce obesity. NLFE reduced the body weight, body lipid accumulation, and activities of fatty acid synthase (FAS), glutamic oxaloacetic transaminase, and glutamic pyruvic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 41 publications
7
75
0
2
Order By: Relevance
“…In normal physiological state, nutritional factors such as high-fat diet and hormone could regulate the enzyme activity and gene expression of the FAS (Rosebrough et al 2011). The level of FAS in the present study was lower in AF's treatment groups than in control group; in liver and adipose tissues in a dose-dependent manner, this is in accordance with previous studies demonstrating that Nelumbo nucifera leaf flavonoid-rich extract targets lipid-regulated enzymes and may be effective in attenuating body lipid accumulation and preventing obesity (Wu et al 2010).…”
Section: Discussionsupporting
confidence: 82%
“…In normal physiological state, nutritional factors such as high-fat diet and hormone could regulate the enzyme activity and gene expression of the FAS (Rosebrough et al 2011). The level of FAS in the present study was lower in AF's treatment groups than in control group; in liver and adipose tissues in a dose-dependent manner, this is in accordance with previous studies demonstrating that Nelumbo nucifera leaf flavonoid-rich extract targets lipid-regulated enzymes and may be effective in attenuating body lipid accumulation and preventing obesity (Wu et al 2010).…”
Section: Discussionsupporting
confidence: 82%
“…Chakravarthy et al (2009) have reported that a low level of FAS could protect mice from diet-induced obesity [33]. The level of FAS in the present study was lower in aloe flavonoids treatment groups than in model group, this is in accordance with previous studies demonstrating that Nelumbo nucifera leaf flavonoid-rich extract targets lipid-regulated enzymes and may be effective in attenuating body lipid accumulation and preventing obesity [34]. But in the liver, the FAS mRNA expression shown no significant decrease when compared with the model group.…”
Section: Discussionsupporting
confidence: 82%
“…6) Their important roles include free radical scavenging, reduction, protection against lipid peroxidation and quenching of the reactive oxygen species. 7) Many compounds in the plant kingdom are reported to exist in glycosidic or glycol form. A previous study has proved that the bioavailability of the aglycone form was higher than the glycoside form for isoflavones.…”
mentioning
confidence: 99%